Formulation Design Of Rapidly Disintegrating Phenobarbitone Tablets By Direct Compression Method - MAHADEVAPPA V. RAMPURE; BASAWARAJ BENDEGUMBLE.; S. APPALA RAJU.; RAGHUNANDAN DESHPANDE; P.V. SWAMY (International Journal of Pharma and Bio Sciences, 2010)
In the present work, fast dissolving phenobarbitone tablets were prepared by direct compression method with a view to enhance patient compliance. The methodology worked out was by using three superdisintegrants (2-8%w/w) i.e., L-hydroxypropyl cellulose (L-HPC), pregelatinized starch, Crospovidone with varying concentration of microcrystalline cellulose(5-15%w/w) were used and directly compressible mannitol (Pearlitol SD 200) was used as a diluent to enhance the mouth feel. The prepared batches of tablets were evaluated for hardness, friability, drug content uniformity and In-vitro dispersion time (approximately 7 s). Three promising formulations were tested for drug release pattern (in pH 6.8 phosphate buffer), short term stability (at 40°/75% RH for three months) and drug-excipient interaction (IR spectroscopy). Among the promising formulations, the formulations FCP3 (containing 8% w/w of crospovidone and 15% w/w of microcrystalline cellulose) emerged as the overall best formulation (t50% 1.45 min) based on the in-vitro drug release compared to conventional commercial tablet (t50% 15 min). Short-term stability studies on the formulations indicated that there are no significant changes in drug content and In-vitro dispersion time.